2015
DOI: 10.1080/03075079.2015.1110692
|View full text |Cite
|
Sign up to set email alerts
|

Focusing the kaleidoscope: exploring distributed leadership in an English university

Abstract: Focusing the kaleidoscope: Exploring distributed leadership in an English universityIn the UK and elsewhere, the idea of 'distributing leadership' in universities is becoming more popular. Yet, there is surprisingly little research on this topic. This paper reports on a funded study which explored how one institution had implemented a newly conceived 'distributed' leadership model, specifically to investigate the impact of the model on the academics who had taken on the new leadership positions within the univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Taken together, these findings suggest that for many associate deans, although they may be responsible for major inter-disciplinary and cross-university projects, they do not have the formal line management and budgetary controls necessary to enact important decisions with any real authority (Owens and Valesky 2011). Similar results have been found in a previous study exploring distributed leadership in a research-led university (Floyd and Fung 2017) and suggests that while such distributed models are increasingly espoused, any real control and accountability in term of line management responsibilities and budgets are not always relinquished from senior managers. This practice may hamper important decisions being made further down the organisational chain and points to the fact that leadership is not being fully distributed.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Taken together, these findings suggest that for many associate deans, although they may be responsible for major inter-disciplinary and cross-university projects, they do not have the formal line management and budgetary controls necessary to enact important decisions with any real authority (Owens and Valesky 2011). Similar results have been found in a previous study exploring distributed leadership in a research-led university (Floyd and Fung 2017) and suggests that while such distributed models are increasingly espoused, any real control and accountability in term of line management responsibilities and budgets are not always relinquished from senior managers. This practice may hamper important decisions being made further down the organisational chain and points to the fact that leadership is not being fully distributed.…”
Section: Discussionsupporting
confidence: 75%
“…This is the case even though, as previously argued, the notion of 'distributing leadership' in universities has become increasingly popular (Bolden et al 2009;Floyd and Fung 2017). Concurring, Bianchini et al (2014, p. 558) identified that more work is needed in this area:…”
Section: Theoretical Underpinnings Distributed Leadershipmentioning
confidence: 89%
“…Relatively little scholarship has focused on educational leadership within informal contexts, where those who facilitate change may not occupy a position that involves formal leadership responsibility. Although the concept of educational leadership within higher education is contested (Bento, 2011;Burke, 2010;Sinha, 2013), there is a body of evidence suggesting that it is best conceptualized as distributed (Bento, 2011;Bolden et al, 2008;Burke, 2010;Floyd & Fung, 2015;Jones, 2014;Jones et al, 2017;van Ameijde, Nelson, Billsberry, & van Meurs, 2009). Distributed leadership theories suggest a departure from traditional hierarchical structures, and advocate for a collaborative approach to leadership that is both spread and shared across an institution (Bolden et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Woods, democracy is a key element of distributed leadership wherein democracy is itself 'dependent on initiatives and influence distributed throughout the organization' (Woods, 2004: 23). In this way, distributed leadership practice including participatory models, if democratically implemented, can signal clear liberal and pluralistic principles across the organization (Floyd and Fung, 2017). In addition, Floyd and Fung suggest that inclusive goals and pluralist values of the institution become more apparent and established when leadership practice is itself democratic.…”
Section: Social Fabric: An Aversion To Differencementioning
confidence: 99%
“…(Hartley, 2007: 204) In recent years, new managerial priorities (e.g. the widening participation agenda, students as paying customers, growing influence of student voice and increased regulation) have resulted in the debate about the potential of participatory models of distributed leadership (Floyd and Fung, 2017;Youngs, 2017) to overcome persistent challenges in the sector. One such development has been the significant increase in the number of black minority-ethnic (BME) students entering HE.…”
Section: Introductionmentioning
confidence: 99%